THE USE OF SNOWBALL THROWING STRATEGY TO IMPROVE THE READING COMPREHENSIONOF THE SECOND YEAR STUDENTS OF MTSAL-MUSLIMUN SEI KIJANG - Siti Azura Azura; Erni '; Supriusman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The aim of this classroom action research was to know whetheror not snowball throwing strategy improve the reading comprehension of the second year students of MTS Al-Muslimun Sei-Kijang.The subjects of this research were27 second year students of MTS Al-Muslimun Sei Kijang. In this research, the data were collected through three ways: test, observation sheets, and field notes. The findings showed that the application of snowball throwing strategy can improve students’ reading comprehension in recount text. At the pre-test, the average score of students was59,85 and got improve after the treatment on the first cycle became 63,23 and improved at the secondcycle became 73,04. Based on the result of the research, English teachers are suggested to use snowball throwing strategy to improve students reading comprehension. Keywords: Snowball Throwing Strategy, Reading Comprehension